The Pull Motivation Factors Of Domestic Tourist To Penang. - Yeoh, Soon Hin (2024)
Domestic tourism constitutes a important element in the sustenance of the sector, particularly during periods of crisis as evidenced by the recent COVID-19 pandemic. Consequently, it is imperative for tourism stakeholders to thoroughly grasp the demographic compositions, characteristics, and underlying motivations of the tourists visiting their destinations. In the absence of a comprehensive understanding of their visitors, the provision of local products and services may fail to align with market expectations, potentially resulting in dissatisfaction with the travel experience. Concurrently, destination managers are required to understand visitors' needs and behaviours in order to formulate effective promotional strategies. This investigation engaged a sample of 504 domestic tourists who had travelled to Penang. The primary objective of this research is to elucidate the demographic profile of domestic tourists and to identify the pull factors that entice them to visit Penang. The data obtained from this survey underwent fundamental statistical analysis to reveal, among other aspects, the levels of assessment regarding selected attributes and categories that draw domestic visitors to this state. The findings of this survey affirm Penang's status as the nation's foremost destination for heritage, culture, and gourmet tourism. This study's results will provide local stakeholders with insights to improve products and services for domestic tourists, thereby maximising satisfaction and fostering a greater intention to return to Penang.